Incidental findings on cone beam computed tomography: Relate and relay - Suhas P Pande; Subhash P Kumbhare; Amit R Parate (Wolters Kluwer Medknow Publications, 2015)
Objective: To evaluate the presence of incidental findings on cone beam computed tomography (CBCT) images and to recognize their clinical importance. Materials and Methods: A total of 700 CBCT scans between January 2013 to August 2014 at Government Dental College and Hospital were evaluated retrospectively. Results: 459 incidental findings (65.57%) were observed in 700 patients. Most common individual incidental finding was mucosal thickening (119) followed by pineal/habenula calcification (99) and choroid plexus (77). Conclusion: The oral and maxillofacial radiologist should carefully interpret all scans and should not ignore the incidental findings and hence avoid untoward snowballing effects.